Patterns of use of hormone replacement therapy in one million women in Britain, 1996-2000. - Million Women Study Collaborators (2002)
OBJECTIVE: To describe national patterns of use of hormone replacement therapy (HRT) in 1996-2000. DESIGN: Population-based study of women aged 50-64. SETTING: England and Scotland. POPULATION: A total of 1,091,250 women were recruited between May 1996 and December 2000. METHODS: Women invited for screening at 66 NHS breast screening units were sent a questionnaire to complete before they were screened; 71% of women screened participated. Prevalence of use of HRT. RESULTS: Overall, 33% of women reported that they were currently using HRT, the average duration of use being 5.8 years; 50% were ever-users. Current use of HRT was about twice as common at age 50-54 than 60-64, but varied little by time or region, the prevalences being 33%-34% in each year from 1996 to 2000; 30% in Scotland and 35% in southeast England. The prevalence of current use of HRT varied substantially depending on the woman's history of gynaecological surgery and past health, and was as follows in women with a history of: bilateral oophorectomy (66%); hysterectomy without bilateral oophorectomy (48%); neither hysterectomy nor bilateral oophorectomy (27%); breast cancer (6%); other cancer (25%); stroke (24%); venous thromboembolism (24%); diabetes (25%); heart disease (31%); or hypertension (31%). There was considerably less variation in the prevalence of use of HRT according to deprivation index, education, parity, body mass index, exercise, smoking or alcohol consumption. CONCLUSIONS: HRT is currently used by around one-third of women aged 50-64 in Britain and appears to be influenced considerably more strongly by a woman's medical and surgical history than by socio-economic or lifestyle factors.